2017
DOI: 10.1016/j.earscirev.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of terracing practices on water erosion control in China: A meta-analysis

Abstract: A B S T R A C TTerracing has long been considered a strategy for soil and water conservation in many mountainous regions of the world. However, the effectiveness of terracing is limited by many factors, such as climate, soil properties, topography, land use, culture, demography and socioeconomic status. The aim of this critical review is to evaluate the roles of terracing on water erosion control in China. A meta-analysis of 601 runoff and 636 sediment observations involving a diversity of terrace structures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 181 publications
(83 citation statements)
references
References 63 publications
0
66
0
1
Order By: Relevance
“…Theoretically, the sediment yield reduction might be synchronized with runoff reduction without the implementation of minimum soil disturbance practices, which means that the sediment yield reduction is approximately equal to the runoff reduction. For terracing practices, the sediment yield reduction is close to the runoff reduction (48.9% for runoff and 53.0% for sediment yield), which indicates that terracing controls water erosion by diminishing runoff and sediment yield synchronously (Chen, Wei, & Chen, ). Terracing practices reduce the velocity and total amount of surface runoff straightforwardly by reshaping the land‐surface morphology (Chen, Liu, & Chen, ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Theoretically, the sediment yield reduction might be synchronized with runoff reduction without the implementation of minimum soil disturbance practices, which means that the sediment yield reduction is approximately equal to the runoff reduction. For terracing practices, the sediment yield reduction is close to the runoff reduction (48.9% for runoff and 53.0% for sediment yield), which indicates that terracing controls water erosion by diminishing runoff and sediment yield synchronously (Chen, Wei, & Chen, ). Terracing practices reduce the velocity and total amount of surface runoff straightforwardly by reshaping the land‐surface morphology (Chen, Liu, & Chen, ).…”
Section: Discussionmentioning
confidence: 89%
“…for runoff and 53.0% for sediment yield), which indicates that terracing controls water erosion by diminishing runoff and sediment yield synchronously (Chen, Wei, & Chen, 2017). Terracing practices reduce the velocity and total amount of surface runoff straightforwardly by reshaping the land-surface morphology (Chen, Liu, & Chen, 2012).…”
Section: The Relationship Of Runoff Reduction and Sediment Yield Rementioning
confidence: 99%
“…The importance of the regulating ES is reflected in the large volume of research highlighting the effectiveness of terraces regarding erosion and flood reduction (e.g. Beach et al, 2002;Gebremichael et al, 2005;zhang & Li, 2014;Chen et al, 2017). Mekonnen et al (2015) identified terraces as sediment retention traps and Wheaton & Monke (1981) considered them the best measure for erosion control.…”
Section: Regulating Ecosystem Servicesmentioning
confidence: 99%
“…Hass et al, 1966;Hammad et al, 2004;Hammad & Børresen, 2006;Wei et al, 2016;Rashid et al, 2016Water Hass et al, 1966Thomas et al, 1980;Chow et al, 1999;Beach et al, 2002;Liu et al, 2004Liu et al, , 2011Schiettecatte et al, 2005;Rashid et al, 2016;Reynes Trias, 2006;Wei et al, 2016 REGULATING Erosion Thomas et al, 1980;Wheaton & Monke, 1981;Chow et al, 1999;Beach et al, 2002;Sharda et al, 2002;Dorren & Rey 2004;Hammad et al, 2004;Gebrernichael et al, 2005;Reynes Trias et al, 2006;Romero Díaz et al, 2007;Chen et al, 2012;Pietsch & Mabit, 2012;Kagabo et al, 2013;Dumbrovsky et al, 2014;zhang & Li, 2014;Arnaez et al, 2015;Mekonnen et al, 2015;Kovár et al, 2016;Rashid et al, 2016;Wei et al, 2016;Arévalo et al, 2017;Chen et al, 2017 Water Thomas et al, 1980;Sandor & Eash, 1995;Chow et al, 1999;Beach et al, 2002;Liu et al, 2004…”
Section: Foodunclassified
See 1 more Smart Citation